Glioblastoma Mimicking Viral Encephalitis Responds to Acyclovir: A Case Series and Literature Review - Piper, Keenan; Foster, Haidn; Gabel, Brandon; Nabors, Burt; Cobbs, Charles (Frontiers in Oncology, 2019)
Viral encephalitis and glioblastoma are both rare conditions with poor prognoses. While the clinical and radiographic presentation of these diseases are often distinctly different, viral encephalitis can sometimes masquerade as glioblastoma. Rarely, glioblastoma can be misdiagnosed as viral encephalitis. In some cases where a high-grade glioma was initially diagnosed as viral encephalitis, antiviral administration has proven effective for relieving early symptoms. We present three cases in which patients presented with symptoms and radiographic findings suggestive of viral encephalitis and experienced dramatic clinical improvement following treatment with acyclovir, only to later be diagnosed with glioblastoma in the region of suspected encephalitis and ultimately succumb to tumor progression.